Implementation of Project Based Learning for Cognitive and Psychomotor Students in the Basic of Workshop Technology Course Welding Sub-competency in the Automotive Engineering Study Program - Rahma Doni; Arif Algifari; Muhammad Irvan (Universitas Negeri Padang, 2022)
The higher education curriculum adopts project-based learning (PjBL) method that emphasizes the provision of knowledge with the problem solving in an organized work project within study group. This is such a solution for the problems of current conventional learning method implementation that made low enthusiasm and slow understanding student especially for Automotive Engineering student in having welding practice in The Basic Workshop Technology Course. By using experimental method in this research to compare conventional learning and PjBL method toward twenty Automotive Engineering students to evaluate cognitive and psychomotor aspect. On the steps, the lecturer starts with provides theoretical enrichment and end with welding practice. To find out the effect of implementing this project-based learning, lecturer divides the class in two study groups by differentiating learning methods, namely the group with conventional learning and the group with PjBL learning. Comparison is made between conventional learning and PjBL learning with projects processed by statistical interpretation. The results of the study showed that there was a significant effect on the results of the psychomotor evaluation of students, but not too significant for the cognitive evaluation results. Based on this research, there is a prove that PjBL is good enough to increase student’s abilities in welding practice as psychomotor representation increment.